2011
DOI: 10.1002/bsl.969
|View full text |Cite
|
Sign up to set email alerts
|

How reason for surgery and patient weight affect verdicts and perceptions in medical malpractice trials: A comparison of students and jurors

Abstract: Jurors' decision-making processes are often influenced by extra-legal factors, including judgments of defendants and plaintiffs. Two studies comparing the decisions of university students with those of community jurors sought to determine if extra-legal factors such as individual differences (including identity as a student or juror participant), the reason for surgery (medically necessary vs. elective), the type of surgery (e.g., gastric bypass, nasal reconstruction) or weight of the patient influenced jurors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The fourth paper reported on mock jurors' decision‐making in medical malpractice cases in which the plaintiffs sued physicians who performed surgeries that went badly. Reichert, Miller, Bornstein, and Shelton () compared the judgments of students and community members acting as mock jurors, varying the reason for surgery (medically necessary vs. elective), the type of surgery (gastric bypass vs. nasal reconstruction), and measured individual difference factors, such as whether participants held negative perceptions of overweight patients who undergo elective surgeries. Although the authors found individual differences between students and community participants in relation to these attributes, those individual differences did not produce results that consistently favored one side over the other.…”
Section: Seven Treatises On Construct and External Validity In Jury Rmentioning
confidence: 99%
“…The fourth paper reported on mock jurors' decision‐making in medical malpractice cases in which the plaintiffs sued physicians who performed surgeries that went badly. Reichert, Miller, Bornstein, and Shelton () compared the judgments of students and community members acting as mock jurors, varying the reason for surgery (medically necessary vs. elective), the type of surgery (gastric bypass vs. nasal reconstruction), and measured individual difference factors, such as whether participants held negative perceptions of overweight patients who undergo elective surgeries. Although the authors found individual differences between students and community participants in relation to these attributes, those individual differences did not produce results that consistently favored one side over the other.…”
Section: Seven Treatises On Construct and External Validity In Jury Rmentioning
confidence: 99%
“…Whether an issue is relevant to the self is likely related to someone’s support for laws related to that issue. Past studies have suggested that relevance to a particular issue is an important consideration (Reichert, Miller, Bornstein, & Shelton, 2011; S. L. Taylor, 2004).…”
Section: Factors Affecting Support For Policymentioning
confidence: 99%
“…One participant characteristic that might be relevant to policy support in the current study is whether the participant is a student or a community member. While previous research has pointed to personal relevance as an explanation for differences between community member and student samples (see Reichert et al, 2011), this study aims to add to this literature by directly examining differences between students and a more diverse sample regarding support for CCT policy, which could affect college students. 1…”
Section: Factors Affecting Support For Policymentioning
confidence: 99%
“…However, differences between the two samples are likely to be more nuanced and context dependent. For example, McCabe and Krauss (2011) found that students were insensitive to differences in the type of risk assessment testimony (clinical versus structured) in a simulated sexually violent predator (SVP) commitment proceeding, whereas venire jurors were differentially influenced by the type of testimony; yet, they also found that the intrinsic cognitive effort could predict verdicts in undergraduates but not venire jurors (see also Reichert, Miller, Bornstein, & Shelton, 2011 for more nuances between samples).…”
Section: Relative Impact Of Clinical Predictions Versus Structured Rimentioning
confidence: 99%